COVID-19 online teaching intervention and learning performance of college foreign language students - Xu, Yufeng; Zou, Yanfen (Frontiers in Psychology, 2023)
This study utilized an online teaching intervention implemented in China 2020 in response to COVID-19 as a quasi-natural experiment, and applied the difference-in-difference model to examine the impact and path of the intervention on students’ learning performance of college foreign language (LPCFL). Based on records of withdrawing and changing courses, classroom learning, and teaching evaluations; a questionnaire survey of teachers and students; and relevant school documents during the last seven terms, the results indicated that the online teaching intervention could significantly improve students’ LPCFL, and this finding remained robust after adopting a placebo test approach to mitigate possible endogeneity issues. Additionally, the study also conducted a group test through sub-sample regression based on students’ discipline characteristics and intervention organization methods. The results showed that the students who took part in the intervention had a significant improvement effect in the three disciplines: humanities had the most significant effect, science and engineering had the least significant effect, and economics and management was in the middle. A range effect was observed for organizational methods The two downward transmission methods by college teaching management term had significant positive effects, while the other two methods of downward transmission by college student management had significant negative effects. Analysis of the action mechanism indicated that the online teaching intervention mostly improved LPCFL through two channels: students’ learning input and learning support. Overall, these findings not only helps to expand the research framework on macro environmental intervention policy and micro learning behavior but also have implications for the in-depth understanding of the real learning effect of online learning interventions for college students and their design in the post-COVID-19 era.